A New Preparation Method for Peroral Endoscopic Myotomy in Patients with Achalasia Can Effectively Reduce the Esophageal Residual Contents: A Comparative Retrospective Study. (3rd February 2022) - Zhang, Zehua; Yan, Xiaohan; Duan, Bensong; Leng, Zhuyun; Zhang, Haibin; Li, Jinze; Zhu, Yinghua; Xu, Meidong; Xu, Qinwei
Abstract : Background and Aim . After routine fasting for patients with achalasia before POEM (peroral endoscopic myotomy) procedure, solid contents may still remain in the esophagus. We aimed to compare the efficacy and patient satisfaction in patients with and without drinking large amounts of carbonated beverages preoperatively. Methods . This retrospective study enrolled 65 achalasia patients who underwent POEM from June 2017 to October 2021. Based on the preoperative diet strategies, patients were divided into carbonated beverage group (n = 48 ) and control group (n = 17 ). Demographic and clinical data, duration of preoperative endoscopy, quality of esophagus cleansing, and patient satisfaction on preoperative procedure were collected and compared. In the current study, we established the quality of esophagus cleansing: Grade A, no remnants or only liquid or frothy discharge; Grade B, a little amount of solid content remained; and Grade C, a large amount of solid content remained. Results . There were 41 Grade A, 6 Grade B, and 1 Grade C patients in the carbonated beverage group, while there were 8 Grade A, 6 Grade B, and 3 Grade C patients in the control group (p value = 0.001). The esophagus cleansing degrees were significantly ameliorated after drinking carbonated beverages in all the three subtypes of achalasia according to the degree of dilatation. The mean duration of preoperative endoscopy was 6.54 ± 2.250 minutes in the carbonated beverage group and 10.27 ± 4.788 minutes in the control group (p value = 0.010). The score of patient satisfaction concerning the procedure before the POEM in the carbonated beverage group was 4.5 ± 0.652, while the score in the control group was 4.35 ± 0.702 (p value = 0.436). In the multivariate analysis, patient satisfaction was significantly associated with male (odds ratio 0.296, 95% CI: 0.097-0.905, p value = 0.033). Conclusions . Drinking carbonated beverages reduce the duration of preoperative endoscopy and ameliorate the esophagus cleansing degrees without impairing patient satisfaction.